ANALISIS PERILAKU SEKSUAL BERISIKO PADA REMAJA TERINFEKSI HIV DAN AIDS - Afritayeni, Afritayeni; Yanti, Penti Dora; Angrainy, Rizka (Jurnal Endurance, 2018)
This time, the most problem of adolescents in Indonesia that consists of 60% adolescents admitted to practice premarital sex and the other that consists of 50% of people living with HIV and AIDS werethe group isadolescents. The negative consequences of sex behavior which causes an Indonesian teenager disrupted opportunities continue study at school, enter the work force, starting become a family and become a member of society as well. Data has taken from Yayasan Sebaya Lancang Kuning that shows HIV-AIDS cases in second largest which provide by teens 15-24. The aim of this is research to analyze factors in high risk sexual behavior in adolescents infected with HIV / AIDS in Pekanbaru. This research is a explanatory research approach with quantitative study. This study was conducted of the month from April to October 2017. The number of samples in this study were that consist of  95 adolescents which infected with HIV / AIDS at the Foundation for Peer Lancang Kuning by sampling technique with accidental sampling technique. Data was collected by using primary and secondary data. Analysis of the data using multivariate analysis with multiple logistic regression test.Based on the results of this study it can be concluded that the most dominant factor affecting teen sexual behavior is sex drivePermasalahan remaja Indonesia saat ini yaitu sebanyak 60% remaja mengaku telah mempraktikkan seks pra nikah dan 50% dari pengidap HIV dan AIDS adalah kelompok usia remaja.Dampak buruk dari perilaku seks  bebas  inilah yang  mengakibatkan remaja Indonesia terganggu kesempatannya untuk melanjutkan sekolah,memasuki dunia kerja, memulai berkeluarga dan menjadi anggota masyarakat secara  baik. Data dari Yayasan Sebaya Lancang Kuning menunjukkan kasus HIV-AIDS terbesar kedua di duduki oleh remaja 15-24 tahun. Tujuan penelitian untuk menganalisis faktor perilaku seksual berisiko pada remaja terinfeksi HIV/ AIDS di  Kota Pekanbaru. Jenis penelitian ini merupakan penelitian eksplanatory research dengan pendekatan kuantitatif.Penelitian ini dilaksanakan dari bulan April-Oktober 2017.Jumlah sampel dalam penelitian ini adalah sebanyak 95 orang remaja yang terinfeksi HIV/ AIDS di Yayasan Sebaya Lancang Kuning dengan teknik pengambilan sampel accidental sampling. Pengumpulan data dilakukan dengan menggunakan data primer dan sekunder. Analisis data menggunakan analisis multivariat dengan uji regresi logistik berganda. Berdasarkan hasil penelitian dapat disimpulkan bahwa faktor yang paling dominan mempengaruhi perilaku seksual remaja adalah dorongan seksual.